Retrotranspositional landscape of Asian rice revealed by 3000 genomes - Marie-Christine Carpentier (Nature Portfolio, 2019)
Transposable elements (TE) are the dominant constituent of plant genomes. Here the authors develop a tool to analyze TE insertion sites in 3000 rice genomes and provide evidence for recent TE activity during cultivation and that external, rather than genetic, stimuli trigger most activations.